2017
DOI: 10.1186/s12954-017-0167-9
|View full text |Cite
|
Sign up to set email alerts
|

How understanding and application of drug-related legal instruments affects harm reduction interventions in Cambodia: a qualitative study

Abstract: BackgroundHarm reduction interventions in Cambodia face numerous obstacles because of conflicting understanding and interests and inconsistencies in the implementation by law enforcement officials. This study aims to examine how understanding and application of Drug Control Law (DCL) and Village/Commune Safety Policy (VCSP) affects harm reduction interventions in Cambodia from the standpoints of law enforcement officials, people who inject drugs and people who use drugs (PWID/PWUD), as well as other key stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…51 A following qualitative study in 2017 also revealed that negative experiences of PWUD, such as being arrested, discriminated or mistreated, have further discouraged and pushed them away from accessing harm-reduction and public health services. 30 In this study, 15.9% PWUD reported having ever been to a drug rehabilitation centre, which refers to the government and NGOs' compulsory detention. According to the standard operating procedures for HIV prevention, care, treatment, and support in prisons and correctional centres in Cambodia, voluntary HIV testing and counselling is provided at the correctional facilities every 6 months.…”
Section: Access To Hiv Intervention and Educationmentioning
confidence: 76%
See 3 more Smart Citations
“…51 A following qualitative study in 2017 also revealed that negative experiences of PWUD, such as being arrested, discriminated or mistreated, have further discouraged and pushed them away from accessing harm-reduction and public health services. 30 In this study, 15.9% PWUD reported having ever been to a drug rehabilitation centre, which refers to the government and NGOs' compulsory detention. According to the standard operating procedures for HIV prevention, care, treatment, and support in prisons and correctional centres in Cambodia, voluntary HIV testing and counselling is provided at the correctional facilities every 6 months.…”
Section: Access To Hiv Intervention and Educationmentioning
confidence: 76%
“… 51 A following qualitative study in 2017 also revealed that negative experiences of PWUD, such as being arrested, discriminated or mistreated, have further discouraged and pushed them away from accessing harm-reduction and public health services. 30 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Misinterpretation of the current HR policies, and the lack of involvement of other community devices with these strategies still exist. [8][9][10] Thus, given the importance of qualifying the understanding of HR strategies -a guideline of the Brazilian mental health policy -to address the consumption of psychoactive substances, and considering the need to understand the challenges that this policy has regarding its operationalization in the health care networks, we propose to investigate the following guiding question: how are harm reduction strategies evaluated in the experience of workers and managers of a Psychosocial Care Network? The research aimed to evaluate the Harm Reduction strategies in the Psychosocial Care Network of a small city in the South of Brazil.…”
Section: Introductionmentioning
confidence: 99%